Nutritional and endocrinologic evaluation of patients with craniopharyngioma. Issue 6 (December 2015) - Nogueira, Mônica Cristina; Berbel Júnior, Alfredo Sérgio; Koenigkam-Santos, Marcel; Moreira, Ayrton Custódio; Nonino, Carla Barbosa; de Castro, Margaret
Summary: Background & aims: Lesions of hypothalamus or adjacent brain structures by the craniopharyngioma (CP) and/or its treatment, as well as changes in orexigenic and anorexigenic hormones, are possible pathogenic factors for the obesity observed in CP patients. This study assessed anthropometric measurements, food intake, and biochemical markers of CP patients. Methods: Weight, height, skinfold thicknesses, circumferences, body composition, food intake evaluation, basal glucose, lipids, insulin, ghrelin, PYY, and HOMA-IR calculation were obtained from CP children (n = 10, 4F, aged 12 ± 4.2yr) and CP adults (n = 27, 13F aged 42 ± 13 yr) and from 32 gender and age matched controls. Results: Overweight/obesity was observed in 51.4% of the patients at the diagnosis and increased to 86.5% at the time of the study. Obesity was more frequent in patients with grade 2 hypothalamic involvement. Most anthropometric measurements were similar in patients and controls. Caloric intake was lower in CP adults, without difference between children. Lipid intake was higher in CP patients. Carbohydrate and protein intakes were lower in CP children, with no difference between adult groups. There were no differences in micronutrients intake as well as in insulin and PYY levels, and HOMA-IR between patients and controls. HDL-c was lower in CP adults and ghrelin higher in CP children. Conclusions: There is a high rate of overweight/obesity in CP patients at the diagnosis and throughout the follow-up period. Obesity was associated with degree of hypothalamic involvement but not with caloric intake. Obesity and a lipid rich diet may have contributed to the dyslipidemia observed in CP patients.